Using Social Media to Communicate in an Emergency Situation - Ashley McLeod-Morin; Ricky Telg; Phillip Stokes; Alena Poulin; Shelli Rampold; Angela B. Lindsey; Sandra Anderson (EDIS)
The Prevent & Protect publication series focuses on the creation of different material formats to resonate with various audiences and ways to maximize their efficacy in communicating risk to the public about mosquito control. This new 4-page publication of the UF/IFAS Department of Agricultural Education and Communication explains how to engage in effective crisis communication and how to effectively use the Prevent & Protect emergency toolkit in a mosquito-related crisis situation. Written by Ashley Mcleod-Morin, Ricky Telg, Phillip Stokes, Alena Poulin, Shelli Rampold, Angela B. Lindsey, and Sandra Anderson. https://edis.ifas.ufl.edu/wc363